Exploring Writing Errors of Beginner EFL Students at CIEX - Castro, Eduviel (CIEX JOURNAL, 2017)
Writing, the most complex language skill on the academic field, is a non-natural ability that involves different important factors such as training, instruction, practice, experience and purpose. There is no guarantee that any people learn to write without some assistance. The idea of carrying out this research was to identify the type of errors students have in common for organizing and classifying them in order to look for strategies by using an error correction model and activities for the development of the writing skill.